Yearbook of the Maimonides Centre for Advanced Studies. 2016 : 2016. - Veltri, Giuseppe; Meyrav, Yoav.; Meyrav, Yoav. (Berlin/Boston : Walter de Gruyter GmbH, 2016)
The Yearbook of the Maimonides Centre for Advanced Studies mirrors the annual activities of staff and visiting fellows of the Centre as well as scholars of the Institute for Jewish Philosophy and Religion at the University of Hamburg and reports on symposia, workshops, and lectures. Although aimed at a wider audience, the yearbook also contains academic articles and book reviews on scepticism in Judaism and scepticism in general.
Intro -- Contents -- Editorial -- Part I: Articles -- Two Kinds of Belief for Classical Academic Scepticism -- Linguistic Scepticism -- The Early Opponents of the Kabbalah and the Role of Sceptical Argumentations: An Outline -- 'The Jews and Their Doubts': Anti-Jewish Polemics in the Fascicolo delle vanità giudaiche (1583) by Antonino Stabili -- Hebraica veritas? Philosophy, Scepticism, and Politics in the Porta Veritatis (1634-1640) -- Misunderstanding Metaphors: Linguistic Scepticism in Mauthner's Philosophy -- Part II: Reports -- Reports of the Fellows -- Proposals of the Fellows -- Reports of the Research Associates -- Activities and Events -- Bibliographical Report -- Report on the Library of Jewish Scepticism.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books